Chemical Castration in Indonesian Criminal Law: Human Rights Perspective: Kebiri Kimia dalam Hukum Pidana Indonesia: Perspektif Hak Asasi Manusia - Kusumawati, Sri Dewi Rahayu; Poernomo, Gatoet (Indonesian Journal of Innovation Studies, 2024)
This study delves into the controversial practice of chemical castration for sexual offenders against children within Indonesian criminal law, examining it through a human rights lens. Adopting a normative legal method, the research incorporates legislative and conceptual analysis with data sourced from primary and secondary legal materials. The study reveals a stark incongruity between chemical castration and rehabilitation goals of the penal system, highlighting its inhumane nature and violation of human dignity. Furthermore, the research discusses the additional sanction of electronic detection devices, scrutinizing its infringement on privacy rights and inconsistency with the International Covenant on Civil and Political Rights (ICCPR). This study underscores the critical need for a penal system that respects human rights while addressing sexual violence against children, calling for a shift from punitive to rehabilitative approaches.Highlights: Chemical castration in Indonesia's penal system conflicts with rehabilitation goals and human rights principles, being inhumane and degrading. The additional use of electronic detection devices infringes on perpetrators' privacy rights and contradicts international human rights conventions. The study advocates for a penal system that balances the need for justice in cases of sexual violence against children with respect for human rights and dignity. Keywords: Human Rights, Chemical Castration, Indonesian Law, Sexual Violence, Penal System